Rural–urban differences in dental opioid prescribing among adolescent/young adult and adult Medicaid beneficiaries - Shoff, Carla; Sheen, Alex; Qu, Luping; Chalmers, Natalia I. (Frontiers in Public Health, 2024)
Introduction There are ongoing concerns about opioid prescribing for surgical and non-surgical dental needs among adolescent/young adult and adult patients. Although there are known differences in the overall opioid prescription rates in rural areas compared to urban areas, the contribution of dental opioid prescriptions is still unclear. This study aims to examine the factors associated with receiving an opioid prescription following a dental visit. Materials and methods This cross-sectional study utilized the 2021 Centers for Medicare & Medicaid Services unredacted Transformed Medicaid Statistical Information System Analytic Files to examine Medicaid and CHIP adolescent/young adult beneficiaries aged 12–20 and adults aged 21–64 who are non-dually eligible for Medicare and had a dental visit in 2021. Multilevel logistic regression models were used to predict the odds of receiving a dental opioid prescription. Results The results of the adolescent/young adult models show that for every percentage point increase in the percentage of non-Hispanic Black residents in a county, the odds of receiving a dental opioid prescription increase by 0.8% in rural areas. However, with every percentage point increase in the Hispanic population, the odds of receiving a dental opioid prescription decrease by 0.3% in rural areas and 0.7% in urban areas. The adult models show that compared to non-Hispanic white beneficiaries, non-Hispanic Black beneficiaries are 8% more likely to receive a dental opioid prescription if they live in rural areas and 18% more likely if they live in urban areas, while all other racial and ethnic groups are significantly less likely to receive a dental opioid prescription. With every unit increase in the concentrated disadvantage index, the odds of receiving a dental opioid prescription increase by 17% among rural adults and 24% among urban adults. Discussion Our findings on rural–urban disparities in opioid prescriptions suggest that prescription patterns in dental settings are significant and inequitable across various beneficiary- and county-level factors and areas of residence. These variations in prescription patterns highlight the known disparities in access to preventive dental care and the need for targeted interventions to address the healthcare needs of rural residents.